APLIKASI PENGHITUNG BERAT BARANG BERBASIS WEB DENGAN METODE NAÏVE BAYES - Datumaya Wahyudi Sumari, Arwin; Farel Putra Hidayat; Mochammad Syaifuddin Zuhri; Muhammad Auful Kirom (Jurnal Mnemonic, 2022)
The sale and purchase of flea goods is a process that we often find in the community. However, these transactions still use the traditional method, where buyers go around looking for people who sell flea goods, so they spend a lot of energy, money, and thought in the transaction. This study aims to make it easier between sellers and buyers in making transactions of any items needed to calculate the weight of the item, especially in flea-goods transactions, so that buyers or consumers do not bother to carry scales everywhere when making transactions. This technology combines real and virtual objects in a real environment, runs interactively in real time, and there is an integration of weight measurement where this application is based on a website, so that it can be run on various smartphones with various specifications and can reach people who need this application. This feature is executed by entering the dimensions of the item, which in the current research focus, the item used is a bottle and then it is submitted so that the results of the calculations on the server side are obtained in the form of the weight of the junk item. Calculation of the weight of the goods using the Naïve Bayes method which aims to predict the results of calculations with a comparison of variables from the dataset that has been determined by measuring the weight of the goods. The accuracy results obtained are 100%.